Deepening integration coordinates of the European Assembly - Bucur, Andreea (Studies and Scientific Researches. Economics Edition, 2010)
The European economic integration is, by its nature, a very complex and multilateral process, representing a wide area for multidisciplinary studies and research. At the same time, in the current context, the European integration acquires new additional valences, reason for which we can say that the significance of issues related to its manifestation is not diminishing but rather increases. Considering the importance and topical of the researched subject, this paper aims to present and highlight the complexity of deepening as a fundamental dimension of European economic integration, and possible consequences resulting from its implementation.